Teknik Marketing E-Comerce Shopee Bisa Mendominasi Pasar E-Comerce di Indonesia - Faqihuddin Tri Wibowo; Muhammad Shidiqi Abiyu Khuzaeni; Divka Avedish; Naerul Edwin Kiky Aprianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Marketing strategy is an important component in managing a business. This article examines the marketing techniques of Shopee's e-commerce to dominate the monopolistic e-commerce market in Indonesia using a qualitative descriptive method through an in-depth literature study, comprehensively reviewing sources such as scientific journals, international journals, and books. Data collection techniques involve interviews with Shopee users. The concept of product marketing through segmentation, targeting, and positioning (STP) as well as the marketing mix provides a useful framework in identifying market opportunities and enhancing the company's competitiveness, while also minimizing potential losses. Marketing strategies consist of direct selling, earned media, point of purchase, and internet marketing. business operators must comply with various prohibitions and regulations set by the government to protect consumers and maintain healthy competition